The preparation, characterization, structure and dissolution analysis of apremilast solvatomorphs. Issue 4 (6th March 2017) - Wu, Yun-Deng; Zhang, Xiao-Lei; Liu, Xiao-Hong; Xu, Jian; Zhang, Mei; Shen, Kun; Zhang, Si-Han; He, Yong-Mei; Ma, Yan; Zhang, Ai-Hua
Abstract : The ability of apremilast (AP) to form solvates has been investigated and three solvatomorphs of AP, namely, with ethyl acetate, toluene and dichloromethane, were obtained. The three AP solvatomorphs were characterized and dissolution analyses were performed to study the dissolution rates of different AP solvatomorph tablets in vitro and to make comparisons with commercial apremilast tablets. Abstract : Apremilast (AP) {systematic name: ( S )‐2‐[1‐(3‐ethoxy‐4‐methoxyphenyl)‐2‐(methylsulfonyl)ethyl]‐4‐acetamidoisoindoline‐1, 3‐dione} is an inhibitor of phosphodieasterase‐4 (PDE4) and is indicated for the treatment of adult patients with active psoriatic arthritis. The ability of AP to form solvates has been investigated and three solvatomorphs of AP, namely, the AP ethyl acetate hemisolvate, C22 H24 N2 O7 S·0.5C4 H8 O2, the AP toluene hemisolvate, C22 H24 N2 O7 S·0.5C7 H8, and the AP dichloromethane monosolvate, C22 H24 N2 O7 S·CH2 Cl2, were obtained. The three AP solvatomorphs were characterized by X‐ray powder diffraction, thermogravimetric analysis and differential scanning calorimetry. Single‐crystal X‐ray diffraction was used to analyze the structures, crystal symmetry, packing modes, stoichiometry and hydrogen‐bonding interactions of the solvatomorphs. In addition, dissolution analyses were performed to study the dissolution rates of different AP solvatomorph tablets in vitro and to make comparisons with commercial apremilast tablets (produced by Celgene); all three solvatomorphs showed similar dissolution rates and similar values of the similarity factor f2 in a comparison of their dissolution profiles.